Performance enhancement of photovoltaic cells by changing configuration and using PCM (RT35HC) with nanoparticles Al2O3. (1st January 2019) - Abdelrahman, H.E.; Wahba, M.H.; Refaey, H.A.; Moawad, M.; Berbish, N.S.
Highlights: Use of PCM, nanoparticles (Al2 O3 ) and heat sink to enhance the PV system performance. Enhancement in temperature reduction of 20–46.3% in front surface temperature using RT35HC. Enhancement in temperature reduction of 52.3% in front surface temperature by adding the nanoparticles. Abstract: The present experimental work aims to enhance the photovoltaic cells performance. The effect of changing configurations and using PCM mixed with nanoparticles are experimentally investigated. PCM (RT35HC) is mixed with various volume fractions of AL2 O3 from 0.11% to 0.77%. Also, cylindrical fins are used as heat sink and thermal conductivity enhancer (TCE) for a heat aluminum plate to simulate PV solar cell. The percentage of the cylindrical fins root area ratio, AR, is varied from 1.29 to 2.57% and the corresponding percentage enclosed area ratio, AE, is changed from 3.57 to 7.14%. The results show that the cylindrical fins with RT35HC achieves enhancement in temperature reduction of 20–46.3% in the front surface temperature and increases to 52.3% by adding the nanoparticles with range of heat flux from 279 W/m 2 to 820 W/m 2 at T∞ =20 ± 1 °C.